Gestão de riscos: uma avaliação do risco de fraude em empresas do comércio varejista de Aracaju - Carmo, Claifton Bongiovani do (2009)
Polls shows that in recent years, the rate of fraud has increased significantly in the world in general. In Brazil, particularly in the retail segment of the loss reaches 2% of gross revenue, which in many cases, represents a considerable impact on the gross revenue of the company. Measuring the loss of fraud is not an easy task, because the organizations do not always have the tools and information to signal the occurrence of fraud. Accordingly, this paper aims to propose and test a methodology to estimate and evaluate the impact of fraud as a risk to the business, taking as reference the model used by financial institutions for allocating capital for operational risk from a field research conducted in a sample of 37 companies in the retailing of Aracaju that act on the segments of building materials, auto parts, computer supplies, pharmacy and drugstore. Based on the estimated value of loss tempered the results indicate that the risk of fraud is greater in the segments of automotive and building materials, and, most of them, is present in the areas of financial and stock. Compared to the national scene, the impact of fraud in the gross revenue of the companies was evaluated, as the segment on values that are up to 40 to 200 times lower than the rate of loss in the Brazilian retail. What can not be ensured on the basis of low absolute reliability of the data, which were obtained through qualitative research.